A facile fabrication of hierarchical Ag nanoparticles-decorated N-TiO2 with enhanced photocatalytic hydrogen production under solar light. (9th February 2016) - Yang, Siyuan; Wang, Hongjuan; Yu, Hao; Zhang, Shengsen; Fang, Yueping; Zhang, Shanqing; Peng, Feng
Abstract: The hierarchical Ag NPs with a bimodal size distribution were auto-decorated on the surface of rice-like N-TiO2 (named h-Ag/N-TiO2 ) by semiconductor-metal double excitation process under solar light irradiation. The photoinduced growth process of self-assembled h-Ag/N-TiO2 and its photocatalytic mechanism of photo-splitting ethanol into hydrogen have been discussed in detail. The synthesized h-Ag/N-TiO2 as a plasmonic photocatalyst for photo-splitting ethanol exhibited a higher hydrogen production rate (4.7 mmol h −1 g −1 ) than Ag NPs universally loaded N-TiO2 (3.4 mmol h −1 g −1 ) and pure N-TiO2 (2.1 mmol h −1 g −1 ). This work presents a reversed photo-induced synthesis strategy to design a stable Ag-TiO2 plasmonic photocatalyst with high photocatalytic efficiency under solar light. A better understanding of this solar light induced self-assembled process for Ag-TiO2 is crucial in developing metal-semiconductor system for solar energy materials. Graphical abstract: Hierarchical Ag NPs with a bimodal size distribution are auto-decorated on the surface of rice-like N-TiO2 (named h-Ag/N-TiO2 ) by a reversed photo-induced synthesis method. The synthesized h-Ag/N-TiO2 as a plasmonic photocatalyst for ethanol photo-splitting exhibits an enhancement photocatalytic hydrogen production rate under solar light. Highlights: The rice-like nitrogen doped titanium dioxide (N-TiO2 ) is synthesized. Hierarchical Ag nanoparticles are auto-decorated on N-TiO2 (h-Ag/N-TiO2 ). The photoinduced growth process of self-assembled h-Ag/N-TiO2 is revealed. Photocatalyst h-Ag/N-TiO2 exhibits a high hydrogen production rate under solar light. Photocatalytic mechanism of photo-splitting ethanol into hydrogen is discussed.